Study of choices of contraception in postpartum women in a tertiary care institute in Mumbai, Maharashtra, India - Farogh, Aliya; Palve, Tushar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This modern era talks about women strength and empowerment where they are working either equally or one step ahead of men. However, a fall back in making decisions for contraception use and family planning can still be observed. It is most frequently seen among women belonging to some village as they are exposed to a minimal health care. Keeping this in mind, this crucial period was considered as opportunity to test the issue regarding the various choices of contraception available. Objective of this study was to find out the criteria and methods of contraception selected by women in the postpartum period. Methods: A cross-sectional study in the department of obstetrics and gynaecology was conducted over a period of 11/2 years in which a total of 150 postpartum women were interrogated and counselled regarding various methods of contraception. Results: The contraceptive methods most commonly selected in postpartum period are PPIUCD, Barrier, tubal ligation and injectable contraception of which condom is the most common method adopted. The important factors responsible for the choice of contraception include parity, breast- feeding, education and socio-economic status of the women. Conclusions: Postpartum period is particularly important for initiating contraception as the largest proportion with unmet need of contraception is found among those in their first year after child birth. In order to space birth in a healthy manner postpartum contraception should be emphasized upon.